El sistema perlas y su incidencia en la toma de decisiones en las COAC - segmento 3, cantón Riobamba, 2018 - Jenny Rocio, Aguagallo Pacheco (2020)
In this research work, an analysis was carried out on CSC (Cooperatives of Savings and Credits), COAC in Spanish, belonging to segment 3 of the Riobamba canton in 2018, by applying the SISTEMA PERLAS in order to determine the critical areas of the CSC that help to make efficient managerial decisions. The content of the research is as follows: Chapter I contains the referential frame that includes the statement of the problem, justification, objectives and hypotheses. Chapter II, includes the state of the art and generalities about cooperativism that contains information on the origin of cooperativism in Ecuador and the segmentation of cooperatives, then, there are definitions of the two study variables that are about the SISTEMA PERLAS and decision making. Chapter III refers to the methodological framework that includes the method, type, design, research approach, population and sample and the techniques and instruments for data collection and interpretation. For chapter IV, which is about the results and discussion, information was collected from the State of Financial Situation and the State of Income of “Cooperativa de Ahorro y Crédito Minga Ltda.” and the “Cooperativa de Ahorro y Crédito San Jorge Ltda.” Finally, chapter V shows conclusions that respond to the proposed objectives and recommendations to improve the financial and economic practices of the cooperatives belonging to segment 3.